2022
DOI: 10.1002/ange.202205858
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Fragment Screening of the SARS‐CoV‐2 Proteome Explores Novel Chemical Space for Drug Development

Abstract: SARS-CoV-2 (SCoV2) and its variants of concern pose serious challenges to the public health. The variants increased challenges to vaccines, thus necessitating for development of new intervention strategies including anti-virals. Within the international Covid19-NMR consortium, we have identified binders targeting the RNA genome of SCoV2. We established protocols for the production and NMR characterization of more than 80 % of all SCoV2 proteins. Here, we performed an NMR screening using a fragment library for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…These tubercidin-derived compounds are less cytotoxic and decrease the activity of nsp16 in biochemical assays (Klima et al 2022; Schultz et al 2022; Li et al 2023) and in the case of SS148 also the activity of nsp14 (Devkota et al 2021). Despite the knowledge of binders and inhibitors together with diverse in silico drug screens (Xu et al 2020; Maurya et al 2020; El Hassab et al 2021; Vijayan et al 2020) and an NMR fragment screen (Berg et al 2022), no selective and effective nsp16 inhibitor has been identified to this point. Crystal structures of nsp10-16 from SARS-CoV, SARS-CoV-2, and MERS-CoV are available (Wilamowski et al 2021; Chen et al 2011, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…These tubercidin-derived compounds are less cytotoxic and decrease the activity of nsp16 in biochemical assays (Klima et al 2022; Schultz et al 2022; Li et al 2023) and in the case of SS148 also the activity of nsp14 (Devkota et al 2021). Despite the knowledge of binders and inhibitors together with diverse in silico drug screens (Xu et al 2020; Maurya et al 2020; El Hassab et al 2021; Vijayan et al 2020) and an NMR fragment screen (Berg et al 2022), no selective and effective nsp16 inhibitor has been identified to this point. Crystal structures of nsp10-16 from SARS-CoV, SARS-CoV-2, and MERS-CoV are available (Wilamowski et al 2021; Chen et al 2011, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Both strategies, while being effective, inevitably tend to be sensitive towards evolutionary pressure to evade the immune response or the antiviral agent. To provide a broader approach, our project Covid19-nmr (Duchardt-Ferner et al 2023), has focused on screening the entire proteome (Berg and Wirtz Martin and Altincekic et al 2022) and RNA genome of SCoV-2 to identify binding fragments for further medicinal chemistry campaigns. One underestimated but promising research area is the development of drugs targeting RNA, which could potentially revolutionize antiviral treatment.…”
Section: Introductionmentioning
confidence: 99%